Core size does not affect blinking behavior of dye-doped Ag@SiO2 core–shell nanoparticles for super-resolution microscopy. Issue 15 (28th February 2020) - Thompson, S.; Pappas, Dimitri
Abstract : Dye-doped nanoparticles have been investigated as bright, luminescent labels for super-resolution microscopy via localization methods. Abstract : Dye-doped nanoparticles have been investigated as bright, luminescent labels for super-resolution microscopy via localization methods. One key factor in super-resolution is the size of the luminescent label, which in some cases results in a frame shift between the label target and the label itself. Ag@SiO2 core–shell nanoparticles, doped with organic fluorophores, have shown promise as super-resolution labels. One key aspect of these nanoparticles is that they blink under certain conditions, allowing super-resolution localization with a single excitation source in aqueous solution. In this work, we investigated the effects of both the Ag core and the silica (SiO2 ) shell on the self-blinking properties of these nanoparticles. Both core size and shell thickness were manipulated by altering the reaction time to determine core and shell effects on photoblinking. Size and shell thickness were investigated individually under both dry and hydrated conditions and were then doped with a 1 mM solution of Rhodamine 110 for analysis. We observed that the cores themselves are weakly luminescent and are responsible for the blinking observed in the fully-synthesized metal-enhanced fluorescence nanoparticles. There was no statistically significant difference in photoblinking behavior—both intensity and duty cycle—with decreasing core size. This observation was used to synthesize smaller nanoparticles ranging from approximately 93 nm to 110 nm as measured using dynamic light scattering. The blinking particles were localized via super-resolution microscopy and show single particle self-blinking behavior. As the core size did not impact blinking performance or intensity, the nanoparticles can instead be tuned for optimal size without sacrificing luminescence properties.